Separation characteristics of white rice in an indented cylinder separator with a baffle. (April 2022) - Meng, Xiangyi; Chen, Heqin; Han, Yanlong; Jia, Fuguo; Chu, Yanhao; Chen, Peiyu; Li, Anqi; Zhao, Hongwei
Abstract : Broken rice can gather in the core of a cylinder during rice grain separation because it is wrapped by whole rice and cannot contact the indents causing low separation efficiency. To improve contact with the indented cylinder by broken rice the actions of a baffle were simulated using the discrete element method. By analysing rice movement in the mixing area under the action of baffle, the mechanism of reducing the segregation of grains, and therefore lack of contact with the indents, was clarified. The simulations showed that effects of blade length on separation characteristics were more obvious, compared with that of the rotational speed of the baffle. Shorter blade lengths and lower rotational speeds were more favourable for separation. Optimal parameters of the baffle were obtained after a comprehensive evaluation of the separation efficiency and loss rate was determined by the intercriteria correlation (CRITIC) method. This study provides a foundation for the design of the baffle and improving separation efficiency of the indented cylinder rice separators. Highlights: Separation of indented cylinder with baffle was simulated by discrete element method. The motion behaviors of rice with or without a baffle were investigated. Effect of blade length and rotation speed on separation characteristics was analyzed. The CRITIC method was used to evaluate separation ability comprehensively. Blade length of 0.54 h and rotational speed of 0.5 v are the optimum.